76.1k views
4 votes
Find the sum. ???? 2 0
−2 3
???? + ????1 5
0 1
????

1 Answer

2 votes

Answer:


\left[\begin{array}{cc}2&0\\-2&3\end{array}\right]+\left[\begin{array}{cc}1&5\\0&1\end{array}\right]=\left[\begin{array}{cc}3&5\\-2&4\end{array}\right]

Explanation:

If you have two matrices:


A=\left[\begin{array}{cc}a&b\\c&d\end{array}\right]\\and\\B=\left[\begin{array}{cc}e&f\\g&h\end{array}\right]

The sum of the matrices is:


A+B=\left[\begin{array}{cc}a+e&b+f\\c+g&d+h\end{array}\right]

In this case we have:


A=\left[\begin{array}{cc}2&0\\-2&3\end{array}\right]\\\\\\B=\left[\begin{array}{cc}1&5\\0&1\end{array}\right]

The sum is:


A+B=\left[\begin{array}{cc}2+1&0+5\\-2+0&3+1\end{array}\right]\\\\\\A+B=\left[\begin{array}{cc}3&5\\-2&4\end{array}\right]

The answer is:


\left[\begin{array}{cc}2&0\\-2&3\end{array}\right]+\left[\begin{array}{cc}1&5\\0&1\end{array}\right]=\left[\begin{array}{cc}3&5\\-2&4\end{array}\right]

User Bret Copeland
by
4.2k points